The Projected Newton Iteration Approach for Computing the Nonnegative Z-Eigenpairs of Nonnegative Tensors (CSIAM Transactions on Applied Mathematics, 2021)
In this paper, we propose a new projected Newton iteration for computingthe nonnegative Z-eigenpairs of nonnegative tensors. We show that the required iteration has a local quadratic convergence. More specially, the formulation aims to solvethe tensor equation arising from the multilinear PageRank problem. Numerical experiments are provided to illustrate the effectiveness and superiority of the proposedapproach.
Keywords: Nonnegative tensor; nonnegative Z-eigenpair; local quadratic convergence; multilinear PageRank.